The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1021/ic010917e
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Diversity Covering 15 Orders of Magnitude in Rates:  Cyanide Exchange on [M(CN)4]2- (M = Ni, Pd, and Pt)1

Abstract: Kinetic studies of cyanide exchange on [M(CN)(4)](2-) square-planar complexes (M = Pt, Pd, and Ni) were performed as a function of pH by (13)C NMR. The [Pt(CN)(4)](2-) complex has a purely second-order rate law, with CN(-) as acting as the nucleophile, with the following kinetic parameters: (k(2)(Pt,CN))(298) = 11 +/- 1 s(-1) mol(-1) kg, DeltaH(2) (Pt,CN) = 25.1 +/- 1 kJ mol(-1), DeltaS(2) (Pt,CN) = -142 +/- 4 J mol(-1) K(-1), and DeltaV(2) (Pt,CN) = -27 +/- 2 cm(3) mol(-1). The Pd(II) metal center has the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…As we descend the periodic table, however, Dq increases markedly, further stabilizing the square planar species, with the result that Pd(CN) 4 2À and Pt(CN) 4 2À have much increased stability relative to five-coordinate intermediates and undergo cyanide exchange much more slowly (Table 8.8). 152,153 For M(H 2 O) 4 2þ , substitution of an aqua ligand by A zÀ takes place some 10 5 -fold faster for M ¼ Pd than for M ¼ Pt; typical rate constants are given in Table 8.9, which also shows that the charge on A is not important-the fastest reactions listed are with neutral thiourea-and hence ion pairing is not a prerequisite for reaction, in contrast to I a processes. Recent evidence 96 that at least one (and probably two) extra water molecule(s) is (are) located at relatively long M-OH 2 distances above (and below) the MO 4 plane in aqueous solution implies that the intimate mechanism may not be the simple A process that is commonly invoked.…”
Section: Substitution In Square Planar Complexesmentioning
confidence: 98%
“…As we descend the periodic table, however, Dq increases markedly, further stabilizing the square planar species, with the result that Pd(CN) 4 2À and Pt(CN) 4 2À have much increased stability relative to five-coordinate intermediates and undergo cyanide exchange much more slowly (Table 8.8). 152,153 For M(H 2 O) 4 2þ , substitution of an aqua ligand by A zÀ takes place some 10 5 -fold faster for M ¼ Pd than for M ¼ Pt; typical rate constants are given in Table 8.9, which also shows that the charge on A is not important-the fastest reactions listed are with neutral thiourea-and hence ion pairing is not a prerequisite for reaction, in contrast to I a processes. Recent evidence 96 that at least one (and probably two) extra water molecule(s) is (are) located at relatively long M-OH 2 distances above (and below) the MO 4 plane in aqueous solution implies that the intimate mechanism may not be the simple A process that is commonly invoked.…”
Section: Substitution In Square Planar Complexesmentioning
confidence: 98%
“…PGM adsorption studies by Vorob'ev-Desyatovskii et al (2012) Monlien et al (2002) suggested that pentacoordinated species for Pt and Pd do occur while Sharpe (1976) proposed Eq. (1) for Pd.…”
Section: Temperaturementioning
confidence: 99%
“…This group have also examined the kinetics of CN Ϫ exchange down the group Ni, Pd and Pt for the square planar complexes [M(CN) 4 ] 2Ϫ and also for protonated species. 223 2 nd order kinetics and an associative mechanism prevail throughout the group for CN Ϫ exchange, but there is an enormous variation in rate constants, quoted as 1 : 7 : 200 000 for Pt, Pd, Ni complexes respectively. From a molecular dynamics study of [Gd(egta)(H 2 O)] Ϫ in aqueous solution, the mean volume determined for the loss of H 2 O (7.2 cm 3 mol Ϫ1 ) is in reasonable agreement with experiment.…”
Section: -Coordinationmentioning
confidence: 99%